The anthropology of sustainability : beyond development and progress - BRIGHTMAN, Marc; LEWIS, Jerome (2017)
This book compiles research from leading experts in the social, behavioral, and cultural dimensions of sustainability, as well as local and global understandings of the concept, and on lived practices around the world. It contains studies focusing on ways of living, acting, and thinking which claim to favor the local and global ecological systems of which we are a part, and on which we depend for survival. The concept of sustainability as a product of concern about global environmental degradation, rising social inequalities, and dispossession is presented as a key concept. The contributors explore the opportunities to engage with questions of sustainability and to redefine the concept of sustainability in anthropological terms. -- 1. Introduction: The Anthropology of Sustainability -- 2. Anthropology at the Time of the Anthropocene: A Personal View of What is to be Studied -- 3. A Threat to Holocene Resurgence is a Threat to Livability -- 4. What can Sustainability do for Anthropology? -- 5. Interlude: Perceiving Human Nature through Imagined Non-Human Situations -- 6. “They call it Shangri-La”: Sustainable Conservation, or African Enclosures? -- 7. Conservation From Above: Globalising Care for Nature -- 8. Different Knowledge Regimes and some Consequences for "Sustainability" -- 9. The Viability of a High Arctic Hunting Community: A Historical Perspective -- 10. Ebola in Meliandou: Tropes of "Sustainability" at Ground Zero -- 11. Anthropology and The Nature-Society-Development Nexus -- 12. The Gaia Complex: Ethical Challenges to an Anthropocentric "Common Future" -- 13. Interlude: Performing Gaia -- 14. Sustaining the Pluriverse: The Political O ntology of Territorial Struggles in Latin America -- 15. Traditional People, Collectors of Diversity -- 16. Local Struggles with Entropy: Caipora and Other Demons -- 17. Redesigning Money to Curb Globalization: Can We Domesticate the Root of All Evil?